2021
DOI: 10.1093/nar/gkab795
|View full text |Cite
|
Sign up to set email alerts
|

scAPAdb: a comprehensive database of alternative polyadenylation at single-cell resolution

Abstract: Alternative polyadenylation (APA) is a widespread regulatory mechanism of transcript diversification in eukaryotes, which is increasingly recognized as an important layer for eukaryotic gene expression. Recent studies based on single-cell RNA-seq (scRNA-seq) have revealed cell-to-cell heterogeneity in APA usage and APA dynamics across different cell types in various tissues, biological processes and diseases. However, currently available APA databases were all collected from bulk 3′-seq and/or RNA-seq data, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the ‘ Nucleic acid databases ’ section, several resources illustrate the trend towards single cell-level data acquisition. Two databases cover alternative polyadenylation (APA): scAPAatlas ( 12 ) offers comprehensive analysis of human and mouse data, including correlation with gene expression and links to RNA-binding proteins or miRNAs on APA-regulated regions; scAPAdb ( 13 ) extends covered species to Arabidopsis and other plants. Elsewhere scEnhancer ( 14 ) offers a single cell perspective of enhancer regions in model organisms while scMethBank ( 15 ) covers DNA methylation in human and mouse and in healthy or cancerous cells, extending the whole organism data previously captured by the same group in MethBank ( 16 ).…”
Section: New and Updated Databasesmentioning
confidence: 99%
“…In the ‘ Nucleic acid databases ’ section, several resources illustrate the trend towards single cell-level data acquisition. Two databases cover alternative polyadenylation (APA): scAPAatlas ( 12 ) offers comprehensive analysis of human and mouse data, including correlation with gene expression and links to RNA-binding proteins or miRNAs on APA-regulated regions; scAPAdb ( 13 ) extends covered species to Arabidopsis and other plants. Elsewhere scEnhancer ( 14 ) offers a single cell perspective of enhancer regions in model organisms while scMethBank ( 15 ) covers DNA methylation in human and mouse and in healthy or cancerous cells, extending the whole organism data previously captured by the same group in MethBank ( 16 ).…”
Section: New and Updated Databasesmentioning
confidence: 99%
“… 11 To explore the regulation of co-transcriptional processing independently of the cellular environment, we investigated 5′-3′ links at the gene level in a single tissue—the brain—in which ATSS and APA are particularly abundant. Since APA isoform usage displays cell-to-cell heterogeneity, 47 and some 3′ ends can be specific to certain cell populations, 48 we assessed whether the 5′-3′ links that we identified in Drosophila heads tend to be expressed in the same cell, or whether on the contrary, distinct isoforms are exclusive to different cell types. Using the Drosophila brain atlas, 49 we evaluated every CIA 3′ end at the single-cell level and quantified the co-occurrence of different 3′ ends of the same gene in each of the 177 cell types described in the dataset.…”
Section: Resultsmentioning
confidence: 99%
“…The transcript isoforms 2C2, 2C2a, and 2C2a′ of the COL6A2 gene use different final exons, resulting in alternative polyadenylation (APA) selection. Considering data from scAPAdb, 10 in addition to the transcriptome analysis results of the control case in Figure 3A , it is indicated that exon 28 in 2C2 is predominantly selected as an APA over exon 28 in 2C2a; in addition to the PAS, U or GU-rich downstream and less well-defined upstream sequence elements are known to enhance cleavage efficiency. 11 APA selection occurs when 2 or more PAS sites are present in the gene.…”
Section: Discussionmentioning
confidence: 97%